MANAJEMEN PENGELOLAAN PENYEDIA JASA PELATIH CABANG OLAHRAGA DI KOTA SEMARANG TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this research is to know the providers of the sports training services with its employability.The approach of this research is descriptive qulitatve. The results of the study are as follows: 1) the management of training providers are good, mare than 50% in every dimension of custumer services who feel stisfred with the eligbiliti service agencies. 2) the managemen of human resources managemen is well, it can be seen from employee’s acerange value/trainer that shaws 80-90, it adjusted by graphic rating scale, there fore includes in cery good catagory with symbol V, and the result in every service agencies. Conclusion:1) management coach management services provider in the city of Semarang Year 2013 has been good, consumer perception of the service agencies showed more than 50% of consumers rate good enough to excellent, Human resource management has been good, if seen from the figures shown on employees' performance is very good category. Suggestions are given as follows (1) for institutions that complete paperwork, and infrastructure to support the management functions, (2) for employees / coaches should always increase the competence and legality as coach, (3) hopeless prescribe rules for the government of the enterprise or service provider and the board wage / minimum wage for trainees.